A fast and flexible nearest-level-equivalent space vector modulation algorithm for three-phase multilevel converters. (June 2020) - Lin, Hongjian; Li, Ruoyu; Zhu, Leilei; Yan, Han; Ma, Lan; Yao, Jiaxuan; Shu, Zeliang
Highlights: Merely one nearest space vector closet to the origin requires to be detected online. Redundant and optimized switching sequences are flexibly generated to achieve the minimum number of switching transitions. Continuous modulation and discontinuous modulation modes are easily obtained. It is more hardware efficient, independent of the level number and suitable for various multilevel converters. Abstract: This paper presents a nearest-level-equivalent space vector modulation (SVM) algorithm for three-phase multilevel converters. The proposed algorithm provides a simple approach to obtain three modulation vectors online based on basic vectors. In addition, the principle of nearest-level modulation (NLM) is applied in the proposed SVM to make its superior performance to the generalized SVM algorithms, which present: (1) Merely one modulation vertex need to be detected and three-phase duty cycles are obtained. Therefore, the unbalanced voltages of inner cell of neutral-point-clamped cascaded multilevel converter (NPC-CMC) can be addressed; (2) Redundant and optimized switching sequences are automatically generated to minimize the number of switching transition; (3) Different modulation modes can be flexibly chosen to optimize the harmonic benefit. The proposed SVM scheme is independent of level numbers and finally verified by simulation and experimental results.